A preparation method for nitrogen-doped multi-walled carbon nanotube-loaded metal Cr electrocatalytic material
By optimizing the preparation process, a high proportion of multi-walled carbon nanotubes doped with pyridinic nitrogen supports transition metal chromium (Cr) electrocatalytic materials, which solves the problem in the existing technology of nitrogen-doped multi-walled carbon nanotubes supporting transition metal electrocatalytic materials in carbon dioxide. The problem of insufficient catalytic performance and stability in the reduction reaction has been achieved, and an efficient and stable CO2 reduction reaction has been achieved.
Patent Information
- Application Number
- CN202411479202.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing nitrogen-doped multi-walled carbon nanotube-loaded transition metal electrocatalytic materials lack catalytic performance and stability in carbon dioxide reduction reaction, which restricts their effectiveness in practical applications.
By optimizing the preparation process and using ultrasonic, stirring and heat treatment steps, a multi-walled carbon nanotube-loaded transition metal chromium (Cr) electrocatalytic material doped with pyridinic nitrogen at a high proportion was developed. The method includes coating multi-walled carbon nanotubes with poly4-vinylpyridine and polyvinylpyrrolidone, and then calcining them in two steps to obtain nitrogen-doped multi-walled carbon nanotubes with a high content of pyridine nitrogen, and heating them in an inert atmosphere. The chromium source material is calcined to support metal Cr.
It has significantly improved the electrocatalytic performance and stability, so that it has higher efficiency and longer service life in the CO2 reduction reaction, can restore CO2 as CO at high selectivity, and has good cycle stability.
Smart Images

Figure CN118996487B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic materials, and in particular to a method for preparing a nitrogen-doped multi-walled carbon nanotube-loaded metal Cr electrocatalytic material. Background Art
[0002] Electrocatalytic materials are increasingly used in energy conversion and environmental protection. Especially in the carbon dioxide reduction reaction (CO 2 RR), the electrocatalytic material can convert CO 2 Reduction into valuable chemicals, thus realizing the recycling of resources. 2 Reduction product selectivity, stability, and catalytic efficiency are key factors. However, current electrocatalytic materials have problems such as low catalytic activity and poor stability, which restricts their practical application.
[0003] Carbon-based materials are widely used in electrocatalytic research due to their good electrical conductivity and chemical stability. However, the activity of pure carbon materials in electrocatalytic reactions is limited, so it is necessary to improve their catalytic performance by doping or compounding with other materials. Nitrogen doping is an effective method to improve the electrocatalytic performance of carbon-based materials. Nitrogen atom doping can increase the conductivity and number of surface active sites of the material, thereby significantly improving the catalytic performance. Especially in the pyridine nitrogen content, the effect of CO 2 The catalytic activity of RR is significantly affected. It has been reported in the existing literature that high proportion of pyridine nitrogen doping can effectively improve the CO 2 RR catalytic activity.
[0004] Loading chromium on nitrogen-doped carbon nanotubes (NCNTs) can further improve the catalytic activity and stability of the material. Transition metals have rich electronic structures and can provide more active sites to improve the catalytic activity of CO. 2 However, how to uniformly load carbon nanotubes and ensure their stability during the reaction remains a challenge.
[0005] At present, the existing methods for preparing M@NCNT catalysts (M is a transition metal) include using HZIF-67 as a template for one-step pyrolysis. Although these methods can produce catalysts with excellent performance, they generally have problems such as complex processes, high costs, and low yields. For example, CN116899605A uses complex processes such as multi-step chemical reactions and high-temperature pyrolysis to prepare Co@NCNT catalysts. Although materials with good microstructures can be obtained, the process is cumbersome and not conducive to large-scale applications. Therefore, developing a simple, efficient, and low-cost method for preparing nitrogen-doped multi-walled carbon nanotubes (NCNT) loaded with transition metal electrocatalysts is of great significance for achieving efficient catalysis.
[0006] CN114695904A discloses a method for preparing a self-supporting nitrogen-doped carbon nanotube-loaded platinum nanoclusters, wherein the structural unit of the carbon nanotube is carbon cloth, nitrogen-doped carbon nanotubes (NCNT) are used as a conductive network, and platinum nanoclusters are used as loads, which are loaded on the nitrogen-doped carbon nanotubes by plasma sputtering deposition technology. The method includes multiple steps, firstly ultrasonically treating the carbon cloth in a potassium permanganate solution, then growing cobalt-iron nanowires by hydrothermal reaction, then annealing in an inert gas atmosphere, and finally loading platinum metal on the surface of the carbon nanotubes by plasma sputtering deposition. Although the method can prepare a catalyst with excellent performance, the process is complicated, the cost is high, and the yield is low, which is not conducive to large-scale production and application. CN116899605A discloses an application of Co@NCNT catalyst in phenol hydrogenation, wherein the preparation steps include dissolving 2-methylimidazole and cobalt nitrate hexahydrate in octanol respectively, then preparing HZIF-67 powder by steps such as solution mixing, centrifugation, washing, and drying, and then further pyrolyzing in H 2 / Ar mixed atmosphere to obtain Co@NCNT catalyst. Although this method can prepare catalysts with good microstructure, the process is cumbersome, time-consuming and costly, and there is H 2 The risk of participation is high and it is difficult to achieve large-scale application.
[0007] The above prior art discloses nitrogen-doped carbon nanotubes loaded with transition metal electrocatalysts. Nitrogen doping can change the electronic structure of carbon nanotubes, increase the conductivity of the material and the number of surface active sites, thereby improving the catalytic performance. In particular, high proportion of pyridine-doped nitrogen can effectively improve CO 2 RR electrocatalytic performance. However, how to achieve high proportion of pyridinic nitrogen doping in carbon nanotubes and uniformly load transition metals while ensuring their stability during the reaction, especially their working stability under different environments, remains a challenge to be solved. Summary of the invention
[0008] In order to solve the existing problems in the nitrogen-doped multi-walled carbon nanotube (NCNT)-loaded transition metal electrocatalysts in the carbon dioxide reduction reaction (CO 2 The catalytic performance and stability of RR are still to be improved. The present invention proposes a method for preparing a transition metal Cr electrocatalyst material loaded with multi-walled carbon nanotubes with a high proportion of pyridine nitrogen. The prepared catalyst significantly improves the electrocatalytic performance and stability through the optimized preparation process of the present invention, making it 2 The RR has higher efficiency and longer service life. The present invention prepares nitrogen-doped multi-walled carbon nanotubes (NCNT) with excellent catalytic activity and stability through simple ultrasound, stirring and heat treatment steps, and further loads transition metal chromium to obtain a high-performance Cr-NCNT catalyst.
[0009] The present invention provides the following technical solutions to solve the above technical problems:
[0010] A method for preparing a nitrogen-doped multi-walled carbon nanotube-loaded metal Cr electrocatalytic material comprises the following steps:
[0011] (S1) ultrasonically dispersing clean surface multi-walled carbon nanotubes and poly (4-vinyl pyridine) in an alcohol solvent, heating to 50-60° C., keeping the temperature and stirring, and evaporating the alcohol solvent under reduced pressure to obtain solid powder I; ultrasonically dispersing solid powder I and polyvinyl pyrrolidone in an alcohol solvent, heating to 50-60° C., keeping the temperature and stirring, and evaporating the alcohol solvent under reduced pressure to obtain solid powder II;
[0012] (S2) calcining the solid powder II under an inert atmosphere to obtain nitrogen-doped multi-walled carbon nanotubes;
[0013] (S3) adding a chromium source and 1,10-phenanthroline to an alcohol solvent to obtain Cr(phen) 2 (OAC) 2 The composite is added with nitrogen-doped multi-walled carbon nanotubes, ultrasonically dispersed, and the alcohol solvent is evaporated under reduced pressure to obtain solid powder III;
[0014] (S4) The solid powder III is calcined in an inert atmosphere, and then acid-washed and water-washed after cooling to obtain a nitrogen-doped multi-walled carbon nanotube-loaded metal Cr electrocatalytic material.
[0015] Further, in step (S1), the surface cleaning treatment of multi-walled carbon nanotubes is to immerse the multi-walled carbon nanotubes in concentrated nitric acid solution, stir to remove impurities and metal residues on the surface of the carbon nanotubes, then wash until the eluate is neutral, dry, and obtain surface-cleaned multi-walled carbon nanotubes. Immersed in nitric acid, not only can remove surface impurities, but also can surface modify active functional groups such as carboxyl, which is conducive to subsequent nitrogen doping. The amount of concentrated nitric acid can fully immerse the multi-walled carbon nanotubes, such as concentrated nitric acid mass is 20-30 times that of multi-walled carbon nanotubes.
[0016] Furthermore, in step (S1), the mass ratio of the surface-cleaned multi-walled carbon nanotubes to poly-4-vinylpyridine is 1:1.5-2.2; and the mass ratio of the solid powder I to polyvinyl pyrrolidone is 1:2-3.
[0017] The inventors unexpectedly found that the multi-walled carbon nanotubes were coated with two side chain nitrogen-containing polymers (poly-4-vinylpyridine and polyvinylpyrrolidone) in sequence, and the nitrogen-doped multi-walled carbon nanotubes with high content of pyridinic nitrogen were obtained after calcination, which was beneficial to improve the CO 2RR electrocatalytic performance. The order of poly (4-vinyl pyridine) and poly (vinyl pyrrolidone) cannot be reversed or carried out simultaneously, otherwise the above purpose cannot be achieved. The possible reason lies in the difference in chemical properties and calcination thermal stability of the two nitrogen-containing polymers. Poly (4-vinyl pyridine) can form stable pyridine nitrogen after high temperature calcination, providing CO 2 The important active sites of the reduction reaction need to be coated first to ensure the generation of active sites. Polyvinyl pyrrolidone is mainly used to increase the thickness and uniformity of the coating layer, but it is easy to decompose during the calcination process and cannot form effective active sites. First use poly 4-vinyl pyridine to form a stable layer, and then use polyvinyl pyrrolidone to increase the uniformity, which is to ensure that the material is stable in CO 2 The key to having high active sites and excellent catalytic performance in reduction reactions.
[0018] Furthermore, in step (S1), the weight average molecular weight of poly-4-vinylpyridine is 4000-7000, and the weight average molecular weight of polyvinylpyrrolidone is 10000-20000.
[0019] Furthermore, in step (S1), the alcohol solvent is selected from at least one of methanol, ethanol, isopropanol, and ethylene glycol, preferably anhydrous ethanol. Ultrasonic dispersion and low-pressure distillation of alcohol solvents are well known in the art, for example, ultrasonic dispersion is performed at an ultrasonic frequency of 40-100 kHz for 0.5-2 hours; low-pressure distillation of alcohol solvents can be performed in a rotary evaporator.
[0020] Further, in step (S2), the inert atmosphere is at least one of nitrogen, argon, and helium, preferably argon. The calcination is a staged calcination, firstly heating to 400-500°C at a heating rate of 5-10°C / min and keeping warm for 2-4h, then heating to 600-800°C at a heating rate of 5-10°C / min and keeping warm for 3-5h. The two-step calcination treatment improves the nitrogen doping efficiency, and the thermal decomposition of poly-4-vinylpyridine and polyvinylpyrrolidone achieves a high proportion of pyridine nitrogen introduction.
[0021] Further, in step (S3), the chromium source is selected from at least one of chromium acetate, chromium nitrate, chromium sulfate, and chromium chloride, and the amount of the chromium source and 1,10-phenanthroline added satisfies the molar ratio of Cr to 1,10-phenanthroline of 1:2-2.1. The ratio of the molar amount of Cr in the chromium source to the mass of the nitrogen-doped multi-walled carbon nanotubes is 1mmol:1-5g, preferably 1mmol:2-3g, such as 1mmol:2.4g.
[0022] Furthermore, in step (S4), calcination is performed by heating the temperature to 600-800°C at a heating rate of 5-10°C / min and maintaining the temperature for 2-5h; pickling is performed by immersing in a hydrochloric acid solution to remove unbound Cr and impurities; and water washing is performed by repeatedly washing with deionized water until neutral.
[0023] The nitrogen-doped multi-walled carbon nanotubes loaded with transition metal electrocatalysts prepared by the above method are 2 Reduction reaction (CO 2 The reaction was carried out at a potential of -0.75 V (vs RHE) with 0.5 M KHCO as the electrolyte. 3 Solution, in CO 2 atmosphere, CO can be converted to 2 The electrocatalytic material prepared by the present invention not only exhibits efficient catalytic activity in the laboratory, but also has good cycle stability, and is expected to be mass-produced and applied in industrial applications, providing a new way for CO 2 It provides new solutions for efficient conversion and utilization.
[0024] The present invention also provides a nitrogen-doped multi-walled carbon nanotube-loaded metal Cr electrocatalytic material prepared by the above preparation method, wherein the XPS fine spectrum of N 1s has the following characteristic peaks: 399.1±0.1 eV, 400.2±0.1 eV, 401.1±0.1 eV, 405±0.1 eV; corresponding to pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and nitrogen oxides, respectively; and the characteristic peak area of 399.1±0.1 eV is the largest, that is, the proportion of pyridinic nitrogen is the highest.
[0025] Compared with other prior arts, the present invention has the following advantages:
[0026] First, the present invention sequentially coats multi-walled carbon nanotubes with two side chain nitrogen-containing polymers, and then calcines them in two steps to obtain nitrogen-doped multi-walled carbon nanotubes with a high content of pyridinic nitrogen, and finally prepares nitrogen-doped multi-walled carbon nanotubes (NCNT) loaded with transition metal electrocatalysts with excellent catalytic performance, and conducts a CO 2 Reduction reaction (CO 2 The catalytic performance of Cr-NCNT catalyst was tested in RR. The Cr-NCNT catalyst showed high efficiency and stable catalytic activity, which could significantly improve the CO 2 Efficiency and product selectivity of RR.
[0027] Second, the present invention avoids the use of a variety of complex reagents, the raw materials are cheap and easy to obtain, and mainly uses water and a small amount of ethanol as solvents, without using other auxiliary reagents or complex chemical vapor deposition equipment. The preparation process is simple and easy to operate, saving a lot of costs and resources. Compared with the traditional liquid phase method, the process design of the present invention is more environmentally friendly and significantly reduces the amount of solvent used.
[0028] 3. The Cr-NCNT catalytic material prepared by the method of the present invention forms a nitrogen-doped multi-walled carbon nanotube structure with a high specific surface area and abundant active sites. This structure has a larger specific surface area and enhances the CO 2 The adsorption performance of Cr-NCNT increases the active sites of the reaction and promotes the mass transfer process. In addition, the uniform distribution of nitrogen doping and transition metals significantly improves the conductivity and stability of the material. In the electrocatalytic reaction, the special structure of high proportion of pyridinic nitrogen helps to reduce the energy barrier of the rate-determining step, thereby obtaining higher catalytic activity and stability. Finally, the Cr-NCNT catalytic material has a good performance in CO 2 RR showed excellent reaction performance and could efficiently and selectively convert CO 2 It is reduced to CO and has good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The XRD patterns of the nitrogen-doped multi-walled carbon nanotube-supported metal Cr electrocatalyst material (Cr-NCNT), multi-walled carbon nanotubes (MWCNTs) and nitrogen-doped multi-walled carbon nanotubes (NCNT) prepared in Example 1;
[0030] Figure 2 This is the full XPS spectrum of Cr-NCNT prepared in Example 1;
[0031] Figure 3 is the XPS fine spectrum of N element of Cr-NCNT prepared in Example 1;
[0032] Figure 4 is the SEM energy spectrum of Cr-NCNT prepared in Example 1;
[0033] Figure 5 This is a photo of Cr-NCNT prepared in Example 1. DETAILED DESCRIPTION
[0034] The present invention is described below by means of specific embodiments, but the present invention is not limited thereto.
[0035] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0036] The weight average molecular weight of poly-4-vinylpyridine is about 7,000, and the weight average molecular weight of polyvinylpyrrolidone is about 15,000.
[0037] Multi-walled carbon nanotubes were purchased from Aladdin with a purity of >99.9%, an outer diameter of 30-80nm, and a length of <10μm.
[0038] Example 1
[0039] (S1) Multi-walled carbon nanotubes (MWCNTs) were added to a 30-fold concentrated nitric acid solution and stirred at room temperature for 2 hours to remove impurities and metal residues on the surface of the carbon nanotubes and to modify certain active groups such as hydroxyl and carboxyl groups on the multi-walled carbon nanotubes. After the treatment, the carbon nanotubes were washed with deionized water until the washing solution was neutral. Finally, the carbon nanotubes were dried in an oven at 80°C to obtain multi-walled carbon nanotubes with clean surfaces. 10g of multi-walled carbon nanotubes (MWCNTs) and 15g of poly (4-vinyl pyridine) were added to 300mL of anhydrous ethanol and ultrasonically dispersed for 30min at an ultrasonic power of 100W and an ultrasonic frequency of 40kHz. The mixed solution was then stirred at 50°C for 1 hour to ensure that the carbon nanotubes were uniformly dispersed and fully mixed with poly (4-vinyl pyridine). The ethanol was then removed at low temperature under reduced pressure using a rotary evaporator to obtain solid powder I. 10 g of solid powder I and 20 g of polyvinyl pyrrolidone were ultrasonically dispersed in 300 mL of anhydrous ethanol, and then the mixture was stirred at 50° C. for 1 hour, and then the ethanol was removed at low temperature under reduced pressure using a rotary evaporator to obtain solid powder II.
[0040] (S2) The obtained solid powder II is placed in an argon atmosphere and heated to 500°C in a tube furnace at a heating rate of 5°C / min and maintained for 2 hours to promote the pyrolysis of the polymer and the doping of nitrogen atoms into MWCNTs. Subsequently, the temperature is further increased to 700°C at a heating rate of 5°C / min and maintained for 5 hours to further improve the nitrogen doping efficiency and obtain nitrogen-doped multi-walled carbon nanotubes (NCNTs) with a high nitrogen content.
[0041] (S3) 1 mmol of chromium (II) acetate and 2.1 mmol of 1,10-phenanthroline were added to 20 mL of ethanol and stirred at 50 °C to obtain Cr(phen) 2 (OAC) 2 The composite was then added with 2.4 g of nitrogen-doped multi-walled carbon nanotubes with a high nitrogen content obtained in step (S2), and stirred at room temperature for 1 hour to ensure that the chromium precursor was in full contact with the NCNT surface, and then a rotary evaporator was used to remove the ethanol under reduced pressure to obtain a chromium-carbon nanotube solid composite.
[0042] (S4) The solid composite obtained in step (S3) is placed in an argon atmosphere, heated to 600°C in a tube furnace at a heating rate of 10°C / min and maintained for 2 hours to promote the uniform embedding of chromium species into the NCNT structure to form a Cr-NCNT electrocatalytic material. After calcination, the product is immersed in a 0.5M hydrochloric acid solution for 2 hours to remove unbound chromium particles and impurities. Subsequently, it is fully washed with deionized water to neutrality to obtain a pure Cr-NCNT catalytic material.
[0043] Figure 1 The XRD patterns of nitrogen-doped multi-walled carbon nanotubes loaded with metal Cr (Cr-NCNT) and multi-walled carbon nanotubes (MWCNTs) and nitrogen-doped multi-walled carbon nanotubes (NCNT) prepared in Example 1 are shown in Figure 1. It can be seen that the two peaks at 25.9° and 43° in the XRD spectrum are attributed to the (100) and (002) reflections of MWCNTs, respectively, and no diffraction with related metals is found, which indicates that both metal and nitrogen elements are uniformly distributed on the carbon nanotubes in a doping manner, and the crystal structure or morphology of the carbon nanotubes is not significantly changed.
[0044] Figure 2 This is the full XPS spectrum of Cr-NCNT prepared in Example 1. The XPS high-resolution spectrum of Cr 2p has characteristic peaks of 587.3±0.1eV and 577.4±0.1eV; the XPS high-resolution spectrum of O 1s has a characteristic peak of 530.2±0.1eV; the XPS high-resolution spectrum of C1s has a characteristic peak of 290.2±0.1eV; and the XPS high-resolution spectrum of N 1s has a characteristic peak of 399.5±0.1eV.
[0045] Figure 3 This is the XPS fine spectrum of N 1s of Cr-NCNT prepared in Example 1. The contents of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen were analyzed in detail in the XPS high-resolution spectrum peak of N 1s. The peaks were found and distinguished by the different XPS binding energies, among which pyridinic nitrogen was 399.1±0.1 eV, pyrrolic nitrogen was 400.2±0.1 eV, graphitic nitrogen was 401.1±0.1 eV, and nitrogen oxide was 405±0.1 eV. Among them, the pyridinic nitrogen peak area was the largest.
[0046] Figure 4 This is the SEM spectrum of Cr-NCNT prepared in Example 1. It clearly shows the presence of N (nitrogen) and Cr (chromium) elements, which are evenly dispersed in the material.
[0047] Figure 5 This is a photo of Cr-NCNT prepared in Example 1, which is in the form of black powder.
[0048] Example 2
[0049] The other conditions were the same as those in Example 1, except that in step (S1), the amount of poly-4-vinylpyridine was changed to 22 g, and the amount of polyvinylpyrrolidone was changed to 30 g.
[0050] Example 3
[0051] The other conditions are the same as those in Example 1, except that step (S2) is changed to: the obtained solid powder II is placed in an argon atmosphere, heated to 400°C in a tube furnace at a heating rate of 5°C / min and maintained for 2 hours to promote the pyrolysis of the polymer and the doping of nitrogen atoms into MWCNTs. Subsequently, the temperature is continued to be increased to 800°C at a heating rate of 5°C / min and maintained for 3 hours to further improve the nitrogen doping efficiency and obtain nitrogen-doped multi-walled carbon nanotubes (NCNTs) with a high nitrogen content.
[0052] Example 4
[0053] The other conditions were the same as those in Example 1, except that step (S2) was changed to: placing the obtained solid powder II in an argon atmosphere, heating it to 700°C in a tube furnace at a heating rate of 5°C / min and maintaining it for 4 hours to promote the pyrolysis of the polymer and the doping of nitrogen atoms into MWCNTs to obtain nitrogen-doped multi-walled carbon nanotubes (NCNTs). That is, no staged heating treatment was performed.
[0054] Comparative Example 1
[0055] The other conditions are the same as those in Example 1, except that in step (S1), after obtaining the multi-walled carbon nanotubes with clean surface, 10g of multi-walled carbon nanotubes (MWCNTs) and 15g of polyvinyl pyrrolidone are added to 300mL of anhydrous ethanol, and ultrasonic dispersion treatment is performed for 30min under the conditions of ultrasonic power 100W and ultrasonic frequency 40kHz, and then the mixed solution is stirred at 50°C for 1 hour to ensure that the carbon nanotubes are uniformly dispersed and fully mixed with poly 4-vinyl pyridine, and then the ethanol is removed at low temperature under reduced pressure using a rotary evaporator to obtain solid powder I. 10g of solid powder I and 20g of poly 4-vinyl pyridine are ultrasonically dispersed in 300mL of anhydrous ethanol, and then the mixed solution is stirred at 50°C for 1 hour, and then the ethanol is removed at low temperature under reduced pressure using a rotary evaporator to obtain solid powder II. The subsequent operation is the same as in Example 1. That is, the order of adding poly 4-vinyl pyridine and polyvinyl pyrrolidone is reversed.
[0056] Comparative Example 2
[0057] The other conditions are the same as those in Example 1, except that in step (S1), after obtaining the surface-cleaned multi-walled carbon nanotubes, 10 g of multi-walled carbon nanotubes (MWCNTs), 15 g of polyvinyl pyrrolidone, and 20 g of polyvinyl pyrrolidone are added to 400 mL of anhydrous ethanol, and ultrasonic dispersion treatment is performed for 30 min at an ultrasonic power of 100 W and an ultrasonic frequency of 40 kHz, and then the mixed solution is stirred at 50° C. for 1 hour, and then the ethanol is removed at low temperature under reduced pressure using a rotary evaporator to obtain a solid powder. The subsequent operation is the same as in Example 1. That is, poly-4-vinyl pyridine and polyvinyl pyrrolidone are added at the same time.
[0058] Comparative Example 3
[0059] The other conditions are the same as those in Example 1, except that in step (S1), after obtaining the surface-cleaned multi-walled carbon nanotubes, 10 g of multi-walled carbon nanotubes (MWCNTs) and 40 g of dicyandiamide are added to 300 mL of ethanol for ultrasonic treatment, and then stirred at 60°C for 5 hours to ensure that the mixture is uniformly dispersed. After stirring, the obtained dispersion is freeze-dried to obtain a solid powder. The subsequent operations are the same as in Example 1. That is, the nitrogen source is changed to dicyandiamide.
[0060] Comparative Example 4
[0061] The other conditions were the same as those in Example 1, except that step (S3) was changed to: 1 mmol of chromium acetate and 2.4 g of nitrogen-doped multi-walled carbon nanotubes with a high nitrogen content obtained in step (S2) were dispersed in 20 mL of ethanol, stirred at room temperature for 1 hour, and then the ethanol was removed under reduced pressure using a rotary evaporator to obtain a chromium-carbon nanotube solid composite. That is, the chromium acetate was not first composited with 1,10-phenanthroline, but was directly dispersed with the nitrogen-doped multi-walled carbon nanotubes.
[0062] Application Examples
[0063] For CO 2 For the reduction reaction test, an electrochemical workstation was used to provide an applied voltage. A three-electrode system was used for catalysis. The working electrode was the Cr-NCNT catalyst electrode prepared in Example 1 above, with an area of 1 cm², the counter electrode was a commercial platinum electrode, and the reference electrode was an Ag / AgCl electrode. During the reduction process, 50 mL of 0.5 M KHCO 3 CO 2 A saturated electrolyte solution was used as the reaction solution. Before starting the reaction, the reaction system was irrigated with CO 2 The gas was purged for 30 min to reach saturation, and the purge flow rate was 20 ml / min to reduce the interference caused by oxygen in the reaction solution. The reduction reaction was carried out at a constant pressure of -0.65 V RHE for a total of 120 min, and the product gas concentration was detected by gas chromatography. The catalyst of Example 1 had a high CO concentration under different conditions: -0.6 V, -0.65 V, -0.7 V, -0.75 V, -0.8 V, -0.85 V 2 Reduction to generate CO and H 2 It can be seen that during the 2h electroreduction process, the Faradaic efficiency of Cr-NCNT for CO was 94.3% at an applied voltage of -0.75 V, and the Faradaic efficiency for H 2The Faraday efficiency of the Cr-NCNT catalyst was 4.8%, and the total Faraday efficiency was as high as 99.1%. The generation efficiency of other gas products (such as methane and ethylene) was also tested under the same conditions, and none of them was detected. These results further prove that the Cr-NCNT catalyst is effective in CO 2 The main product in the reduction reaction is CO, which has extremely high selectivity.
[0064] Table 1 Effect of Cr-NCNT of Example 1 on CO Faradaic efficiency at different voltages
[0065] .
[0066] We also explored the stability of the Cr-NCNT catalyst of Example 1. The Cr-NCNT prepared in Example 1 was subjected to a stability test experiment for 50 hours at a voltage of -0.75V (vs RHE). At the 50th hour, the CO Faraday efficiency was still above 90%. This is due to the stable structure and excellent conductivity of the Cr-NCNT of the present invention. Its chemical composition and chemical state are stable during the catalytic process, and the active components do not lose. It has excellent stability and durability, and has the potential for scale-up production and practical application.
[0067] Table 2 CO Faraday efficiency of catalyst working time in Example 1
[0068] .
[0069] Under the same conditions, the catalyst electrode was replaced with the Cr-NCNT catalyst prepared in other examples and comparative examples. The results are shown in Table 3 below:
[0070] Table 3 Catalyst performance test
[0071] .
[0072] It can be seen that the catalyst prepared by the present invention has excellent carbon dioxide reduction catalytic activity, high carbon monoxide selectivity, and catalyst stability. This is due to the fact that the multi-walled carbon nanotubes are coated with two side chain N-containing polymers (poly 4-vinyl pyridine and polyvinyl pyrrolidone) in sequence, first using poly 4-vinyl pyridine to form a stabilizing layer, and then using polyvinyl pyrrolidone to increase uniformity, which is to ensure that the material is stable in CO 2 The key to having high active sites and excellent catalytic performance in reduction reactions.
Claims
1. A method for preparing a nitrogen-doped multi-walled carbon nanotube-loaded metal Cr electrocatalytic material, characterized in that: The following steps are involved: (S1) ultrasonically dispersing clean surface multi-walled carbon nanotubes and poly (4-vinyl pyridine) in an alcohol solvent, heating to 50-60° C., keeping the temperature and stirring, and evaporating the alcohol solvent under reduced pressure to obtain solid powder I; ultrasonically dispersing solid powder I and polyvinyl pyrrolidone in an alcohol solvent, heating to 50-60° C., keeping the temperature and stirring, and evaporating the alcohol solvent under reduced pressure to obtain solid powder II; (S2) calcining the solid powder II under an inert atmosphere to obtain nitrogen-doped multi-walled carbon nanotubes; the calcination is performed in stages, firstly heating the temperature to 400-500° C. at a heating rate of 5-10° C. / min and keeping the temperature for 2-4 hours, then heating the temperature to 600-800° C. at a heating rate of 5-10° C. / min and keeping the temperature for 3-5 hours; (S3) adding a chromium source and 1,10-phenanthroline to an alcohol solvent to obtain a Cr(phen)2(OAC)2 complex, adding nitrogen-doped multi-walled carbon nanotubes, ultrasonically dispersing, and distilling off the alcohol solvent under reduced pressure to obtain a solid powder III; the chromium source is chromium acetate, and the amount of the chromium source and 1,10-phenanthroline added satisfies a molar ratio of Cr to 1,10-phenanthroline of 1:2-2.1; (S4) The solid powder III is calcined in an inert atmosphere, and then acid-washed and water-washed after cooling to obtain a nitrogen-doped multi-walled carbon nanotube-loaded metal Cr electrocatalytic material; the calcination is carried out by heating the temperature to 600-800°C at a heating rate of 5-10°C / min and keeping the temperature for 2-5h.
2. The preparation method according to claim 1, characterized in that: In step (S1), the surface cleaning treatment of the multi-walled carbon nanotubes is performed by immersing the multi-walled carbon nanotubes in a concentrated nitric acid solution.
3. The preparation method according to claim 1, characterized in that: In step (S1), the mass ratio of the surface-cleaned multi-walled carbon nanotubes to poly-4-vinylpyridine is 1:1.5-2.2; the mass ratio of the solid powder I to polyvinyl pyrrolidone is 1:2-3.
4. The preparation method according to claim 1, characterized in that: In step (S1), the weight average molecular weight of poly-4-vinylpyridine is 4000-7000, and the weight average molecular weight of polyvinylpyrrolidone is 10000-20000.
5. The preparation method according to claim 1, characterized in that: In step (S1), the alcohol solvent is selected from at least one of methanol, ethanol, isopropanol and ethylene glycol.
6. The preparation method according to claim 1, characterized in that: In step (S2), the inert atmosphere is at least one of nitrogen, argon and helium.
7. The preparation method according to claim 1, characterized in that: In step (S3), the ratio of the molar amount of Cr of the chromium source to the mass of the nitrogen-doped multi-walled carbon nanotubes is 1 mmol: 1-5 g.
Citation Information
Patent Citations
Preparation method of Co-coated NCNTs catalyst and application of Co-coated NCNTs catalyst in phenol hydrogenation
CN116899605A